A win-stay-lose-learn mechanism based on aspiration can promote cooperation in a multigame. (June 2022) - Chu, Chen; Cui, Simin; Yuan, Zheng; Yu, Chunbin
Abstract: A major current focus in solving social dilemmas is how to ensure the sustainability of cooperation. In this work, we extend the traditional aspiration-based win-stay-lose-learn updating rule. Specifically, players maintain not only the strategy but also the game type if their payoffs are larger than the aspiration; otherwise, they synchronously change the game type and adopt a new strategy. We find that the present rule remarkably facilitates the evolution of cooperation and can maintain high cooperation given a large temptation to defect. The potential reason can be explained by the game transition caused by each player's aspiration. Highlights: An extended aspiration-based win-stay-lose-learn updating rule is proposed. When a player is dissatisfied, it will change game type and learn strategy, otherwise keep the game type and strategy. In our work, cooperation can not only survive but also flourish even with a large temptation under some conditions. In a moderate aspiration, all players playing PDG change to SDG, which leads to high cooperation.